Small groceries in Viet Nam - de Brauw, Alan; The Anh, Dao; Tho, Pham Thi Hanh (International Food Policy Research Institute, 2024)
The food environment represents the place in which demand for food meets supply—consumers purchase foods in the food environment, while retailers of the food consumers purchase represent the end of the value chain. In many countries, the food environment is undergoing rapid change as economies grow and populations urbanize; a consequence is that a larger share of food consumed is purchased by the end consumer (de Bruin and Holleman 2023). Viet Nam is no different. Viet Nam’s growing and urbanizing economy has, over time, led to a changing food environment. This note focuses on one type of retailer in Viet Nam’s food environment: the small grocery. We define small groceries as stores that are not supermarkets, are not part of a chain, and have a fixed storefront from which they do business on a daily or near daily basis. These stores play a small but important role in Viet Nam’s food environment, particularly in rural areas, and as we will demonstrate, almost all these groceries sell at least one component of a sustainable healthy diet. As a result, what they sell could help play a role in improving the diets of Viet Nam’s population. To focus on learning more about small groceries, this note makes use of two datasets. One is a listing exercise that enumerated all the businesses selling food in sampled wards of three districts: Dong Da, in urban Ha Noi; Dong Anh, which is in peri-urban Ha Noi; and Moc Chau, which is a rural district northwest of Ha Noi. The second survey used the first survey as a sample frame, and was specifically designed to learn about the constraints and opportunities that micro-, small-, and medium-sized enterprises (MSMEs) face in considering selling more healthy foods (Ceballos et al. 2023). Small groceries are one type of business in the food environment, and all can be considered MSMEs.